A Crohn’s Disease Patient with Extraintestinal Manifestations: A Case Report - Yhan Batista; Herry Purbayu (The Indonesian Society for Digestive Endoscopy, 2021)
Crohn’s disease (CD) is a chronic debilitating inflammatory disease which mostly affect gastrointestinal tract, but due to its unique features, CD enables to affect extraintestinal organs. Pathophysiology of extraintestinal manifestations is still debatable as many experts propose immune-related hypotheses. It is still unpredictable which manifestation precedes another as studies ongoing. Diagnosing CD is difficult since no gold standards available, therefore clinicians must combine history taking, diagnostic modalities, and a good clinical judgement to diagnose CD. Treatment for CD is not only to treat disease activity, but also to prevent complications to preserve patients’ quality of life.